Magnetic Abrasive Finishing of Beta-Titanium Wire Using Multiple Transfer Movement Method - Sung Sik Nam; Jeong Su Kim; Sang Don Mun (Applied Sciences, 2020)
Titanium is often used in various important applications in transportation and the healthcare industry. The goal of this study was to determine the optimum processing of magnetic abrasives in beta-titanium wire, which is often used in frames for eyeglasses because of its excellent elasticity among titanium alloys. To check the performance of the magnetic abrasive finishing process, the surface roughness (Ra) was measured when the specimen was machined at various rotational speeds (700, 1500, and 2000 rpm) in the presence of diamond paste of various particle sizes (0.5, 1, and 3 μm). We concluded that the surface roughness (Ra) was the best at 2000 rpm, 1 μm particle size, and 300 s processing time, and the surface roughness of β-titanium improved from 0.32 to 0.05 μm. In addition, the optimal conditions were used to test the influence of the finishing gap, and it was found that the processing power was superior at a gap of 3 mm than at 5 mm when processing was conducted for 300 s.